Analysis of WNT4 polymorphism in Chinese Han women with endometriosis. Issue 4 (April 2015) - Wu, Zhangying; Yuan, Ming; Li, Yan; Fu, Fangfang; Ma, Wenqinq; Li, Haixia; Wang, Wenwen; Wang, Shixuan
Abstract Endometriosis is a complex disease that is influenced by genetic and environmental factors. In endometriosis, WNT4 plays a likely role owing to its biological functions. In this study, the TaqMan allelic discrimination technique was used to investigate the relationship between endometriosis and four single nucleotide polymorphisms in WNT4 (rs7521902 [A/C], rs16826658 [G/T], rs7515106 [C/T] and rs2235529 [A/G]) in Chinese Han women. A total of 646 patients with endometriosis and 766 normal controls were recurited. Regression analyses revealed that rs2235529 was a risk locus for endometriosis (P = 1.80E-03, OR, 95% CI = 1.311, 1.129 to 1.522), particularly in patients with stage III and IV disease. No significant association was found between endometriosis and rs7521902 (A/C), rs16826658 (G/T), or rs7515106 (C/T). For each of the four single nucleotide polymorphisms, no association was found between patients with endometriosis-related infertility or primary infertility and the controls. The results demonstrated that WNT4 rs2235529 is associated with endometriosis in Chinese Han women, which may result in aberrant expression of WNT4, leading to the pathogenesis of endometriosis.